2000
DOI: 10.1901/jaba.2000.33-299
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responding in the Presence and Absence of Discriminative Stimuli During Multielement Functional Analyses

Abstract: We evaluated the extent to which discriminative stimuli (S D s) facilitate differential responding during multielement functional analyses. Eight individuals, all diagnosed with mental retardation and referred for assessment and treatment of self-injurious behavior (SIB) or aggression, participated. Functional analyses consisted of four or five assessment conditions alternated in multielement designs. Each condition was initially correlated with a specific therapist and a specific room color (S D s), and sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 11 publications
1
69
0
1
Order By: Relevance
“…To facilitate discrimination between functional analysis conditions, we paired each condition with a unique, color-correlated shirt worn by the therapist throughout the session (Conners et al, 2000). The functional analysis continued until we identified one or more clear functions for each child's destructive behavior.…”
Section: Study 1: Functional Analysis and Fct Evaluationmentioning
confidence: 99%
“…To facilitate discrimination between functional analysis conditions, we paired each condition with a unique, color-correlated shirt worn by the therapist throughout the session (Conners et al, 2000). The functional analysis continued until we identified one or more clear functions for each child's destructive behavior.…”
Section: Study 1: Functional Analysis and Fct Evaluationmentioning
confidence: 99%
“…In the current study, there was differential responding during the functional analysis conditions when the discriminative stimulus (i.e. the academic activity) was present (Conners et al, 2000). Future research should evaluate the use of a modified attention condition in typically functioning children in an academic situation if an attention function is suspected but the traditional attention condition does identify attention maintained problem behavior.…”
Section: Discussionmentioning
confidence: 72%
“…Specific stimuli (different experimenters, colored shirts, and session areas) were associated with each FA condition to enhance discrimination of the contingencies in effect (Conners et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Other research has shown that discriminative stimuli (S D s) may facilitate differential responding during multielement FAs by making differences among conditions more salient. Conners et al (2000) showed that correlating S D s, such as different therapists and room colors, with each condition produced either faster or clearer results for four of eight subjects. This procedure is noteworthy because it exemplifies a simple antecedent manipulation that may increase the likelihood of obtaining clear outcomes during multielement FAs.…”
mentioning
confidence: 95%